КОМПЬЮТЕРНЫЙ ЭКСПЕРИМЕНТ С ИСПОЛЬЗОВАНИЕМ ФОРМУЛ ПЛАНКА И РЕЛЕЯ-ДЖИНСА ДЛЯ ОЦЕНКИ ГРАНИЦ КВАНТОВЫХ И КЛАССИЧЕСКИХ ЗАКОНОМЕРНОСТЕЙ ПРИ ПРЕПОДАВАНИИ КУРСОВ ОПТИКИ И АТОМНОЙ ФИЗИКИ - Хожаназарова, Р.М. (SCIENCE and SOCIETY, 2020)
The article is devoted to the issues of demonstrating the results of computer calculations using the Planck and Rayleigh-Jeans formulas in order to identify the limits of applicability of quantum and classical laws in the process of conducting a computer experiment using the Mathematics computer algebra system.
Keywords: methods of teaching Physics; Planck formula; Rayleigh-Jeans formula; Mathematics computer algebra system; comput- er experiment